Market Structure and Cyclical Fluctuations in U.S. Manufacturing: Reply - Domowitz, Ian; Hubbard, R. Glenn; Petersen, Bruce C. (The Review of Economics and Statistics, 1993)
The authors reply to the comment by D. R. Kamerschen and J. Park on their 1988 paper published in this Review. They find that the econometric point raised by these authors is flawed, because differences in model structure and data are ignored. In particular, the importance of materials input in assessing price-cost margins is reiterated here and illustrated with the 1988 paper's original table. Other points of the comment are refuted by direct reference to statistical results and inferred conclusions in the 1988 paper. Copyright 1993 by MIT Press.